A brief review concerning the latest advances in the influence of nanoparticle reinforcement into polymeric-matrix biomaterials. Issue 14 (21st September 2020) - Montanheiro, Thaís Larissa do Amaral; Ribas, Renata Guimarães; Montagna, Larissa Stieven; Menezes, Beatriz Rossi Canuto de; Schatkoski, Vanessa Modelski; Rodrigues, Karla Faquine; Thim, Gilmar Patrocínio
Abstract: Nanoparticles (NPs) have been studied for a wide variety of applications, due to the elevated surface area and outstanding properties. Several types of NPs are available nowadays, each one with particular characteristics and challenges. Bionanocomposites, especially composed by polymer matrices, are gaining attention in the biomedical field. Although, several studies have shown the potential of adding NPs into these materials, some investigation is still needed until their clinical use for in vivo application is consummated. Besides that, is essential to evaluate whether the addition of nanoparticles changes the matrix property. In this review, we summarize the latest advances concerning polymeric bionanocomposites incorporated with organic (polymeric, cellulosic, carbon-based), and inorganic (metallic, magnetics, and metal oxide) NPs. GRAPHICAL ABSTRACT: